2019
DOI: 10.1111/dmcn.14348
|View full text |Cite
|
Sign up to set email alerts
|

Hospital admissions in children with developmental disabilities from ethnic minority backgrounds

Abstract: Aim To compare hospital admission patterns after the first year of life in Australian children with developmental disabilities and children with no known disability, according to maternal country of birth and Indigenous status. Method This was a retrospective cohort study using linked data across health, disability, and hospital admission databases. The study investigated 656 174 children born in Western Australia between 1983 and 2008 with a total of 1 091 834 records of hospital admissions. Results Children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Children with intellectual disability have distinct vulnerabilities. For example, they are at a higher risk for accidents at home, various medical complications, and they have greater frequency of hospitalization for these accidents or complications 1 . Mimmo et al 2 .…”
mentioning
confidence: 99%
“…Children with intellectual disability have distinct vulnerabilities. For example, they are at a higher risk for accidents at home, various medical complications, and they have greater frequency of hospitalization for these accidents or complications 1 . Mimmo et al 2 .…”
mentioning
confidence: 99%
“…In this issue, Abdullahi et al . attempt to bridge the sizeable research gap located at the complex intersection of social and disability‐related healthcare disparities.…”
mentioning
confidence: 99%
“…This was nearly twice the rate of Australian‐born non‐Indigenous children without disability and the overall rate of hospitalization for children without disability. Among Australian‐born children with disability, Abdullahi et al . found that children of foreign‐born mothers who relocated to Australia from low‐income countries had the highest hospital admissions rates, closely followed by children from Indigenous backgrounds.…”
mentioning
confidence: 99%
See 2 more Smart Citations